Generation and characterization of Lhx9‐GFPCreERT2 knock‐in mouse line. Issue 9 (12th August 2014) - Balasubramanian, Revathi; Bui, Andrew; Xie, Xiaoling; Deng, Min; Gan, Lin
Summary LHX9 is a LIM‐homeodomain transcription factor essential for the development of gonads, spinal cord interneurons, and thalamic neurons to name a few. We recently reported the expression of LHX9 in retinal amacrine cells during development. In this study, we generated an Lhx9‐GFPCreERT2 (GCE) knock‐in mouse line by knocking‐in a GCE cassette at the Lhx9 locus, thus inactivating endogenous Lhx9. Lhx9GCE/+ mice were viable, fertile, and displayed no overt phenotypical characteristics. Lhx9GCE/GCE mice were all phenotypically female, smaller in size, viable, but infertile. The specificity and efficacy of the Lhx9‐GCE mouse line was verified by crossing it to a Rosa26‐tdTomato reporter mouse line, which reveals the Cre recombinase activities in retinal amacrine cells, developing limbs, testis, hippocampal neurons, thalamic neurons, and cerebellar neurons. Taken together, the Lhx9‐GCE mouse line could serve as a beneficial tool for lineage tracing and gene manipulation experiments. genesis 52:827–832, 2014. © 2014 Wiley Periodicals, Inc.